Cardiac implications of chicken wooden breast myopathy - Thea Parsberg Støle; Andreas Romaine; Thea Kleiberg; Vibeke Høst; Marianne Lunde; Almira Hasic; Tiril Aurora Lintvedt; Karen Wahlstrøm Sanden; Svein O. Kolset; Jens Petter Wold; Addolorata Pisconti; Sissel Beate Rønning; et al. (Frontiers in Physiology, 2025)
IntroductionWooden breast disease is a myopathy of the skeletal muscle in chickens of commercial breeding. Although the underlying pathophysiology remains unknown, we and others have previously shown that affected broilers display varying degrees of fibrosis, extracellular matrix (ECM) remodeling, inflammation, and alterations in various molecular signaling pathways. Other myopathy conditions, such as Duchenne muscular dystrophy, also affect the cardiac muscle and are associated with fibrosis and reduced cardiac function. To determine potential cardiac implications of wooden breast disease and identify whether molecular and fibrotic changes were similar to what we have previously found in the breast, we have investigated the hearts of commercial Ross 308 broilers.MethodsHearts from male Ross 308 broiler chickens from mildly and severely wooden breast-affected chickens categorized in previous studies were analyzed. Ventricles from the hearts were analyzed by immunoblotting, real-time qPCR, near-infrared spectroscopy, Raman spectroscopy, and Masson`s trichrome histology. RNA sequencing was also conducted to identify the molecular footprint of the mildly and severely wooden breast-affected chickens.ResultsCompared to mildly affected chickens, the severely wooden breast-affected chickens did not show an increase in heart weight, water-binding capacity, or macronutrient composition. The hearts did also not display any differences in fibrosis development, extracellular matrix gene expression, or typical cardiac and inflammatory markers. The severely affected chickens did, however, show a reduction in protein levels of biglycan and fibromodulin, as well as alterations in matrix metalloproteinase 2, Wnt ligands, mTOR signaling, heat shock protein 70, and muscle LIM protein. Functional enrichment analysis of RNA sequencing also suggested a different molecular footprint of biological processes and pathways between the two groups.ConclusionHearts from wooden breast-affected chickens did not display the same fibrotic alterations as those previously found in the breast. Despite few alterations detected in the markers and signaling molecules tested, RNA sequencing indicated a different molecular footprint in the hearts of severely compared to mildly wooden breast-affected chickens.